Surgical management and minimally invasive approaches for the treatment of metastatic sarcoma - Hohenberger, Peter; Kasper, Bernd; Ahrar, Kamran (Educational book, 2013)
Soft tissue sarcomas describe a very heterogeneous group of soft tissue tumors mainly arising in the lower extremities. If diagnosed at an early stage and a complete resection of the primary tumor is achieved, the patients' prognosis is excellent. However, metastatic tumor spread is common with only limited treatment possibilities. Despite an improved insight into tumor biology of sarcomas, no notable improvement has been gained in the last 20 years regarding prognosis of patients. Metastatic lung disease has long been the preserve of systemic treatments, local treatments being considered in a purely palliative intention. Several studies have objectified benefit to the local treatment of metastases, especially in an oligometastatic state. The development of techniques for stereotactic radiotherapy on the one hand and the refusal or contraindication for surgery on the other hand inaugurated studies in this direction. Besides surgery and radiotherapy, other local modalities have been investigated in the last few years such as thermal therapy (radiofrequency and laser ablation) or combined modalities (isolated limb perfusion and deep-wave hyperthermia plus chemotherapy) to help patients with metastatic soft tissue sarcoma. Minimally invasive, image-guided therapies such as thermal ablation should be considered particularly in patients who are not suitable surgical candidates or may have exhausted all other viable surgical options. Some of these techniques will be reviewed in this article, and their value for the patients will be evaluated in the light of indication from tumor biology and technical feasibility. These highly selected and specific procedures should only be performed after decision making in an interdisciplinary sarcoma-board.
Gesehen am 22.12.2021